The Influence of Brand Image, Brand Trust and Brand Awareness on Consumer Loyalty at Excel Pet Food at Fish Centre Lamongan - Hisyam Sathori (RTTM, 2024)
This study aims to determine the influence of Brand Image, Brand Trust and Brand Awareness on Consumer Loyalty on Excel Pet Food at Fish Center Lamongan. The population in this study is all consumers who buy Excel Pet Food at Fish Cenre Lamongan from August to October which is 1,862, and the sample used is 95 respondents. The sample technique uses purposive sampling using the slovin formula. The analysis technique used in this study is linear regression analysis and for hypothesis testing, namely the t test and the F test. Based on the results obtained from SPSS Version 25, it can be concluded from the t test that the variables Brand Image, Brand Trust and Brand Awareness partially have a significant influence on Consumer Loyalty in Excel Pet Food at Fish Center Lamongan, while through the results of the F test, it is known that the variables Brand Image, Brand Trust and Brand Awareness simultaneously have a significant influence on Consumer Loyalty on Excel Pet Food at Fish Center Lamongan.